Pharmacist-led screening in sexually transmitted infections: current perspectives - Wood H; Gudka S (Dove Medical Press, 2018)
Helen Wood, Sajni Gudka School of Allied Health, Faculty of Health and Medical Sciences, The University of Western Australia, Perth, WA, Australia Introduction: Sexually transmitted infection (STI) screening is a crucial initiative that aims to reduce the increasing global prevalence of many common STIs such as chlamydia, gonorrhea, and herpes simplex virus (HSV). Many STIs are either asymptomatic or show mild symptoms that are often attributed to other infections; hence, screening is the only way to identify – and by extension, treat – them. In this way, the spread of STIs can be reduced, and the health implications of an untreated STI are minimized. Community pharmacies could provide an avenue to convenient, confidential STI screening by using noninvasive or minimally invasive sample collection techniques that are used by the consumer or pharmacist. We identified the most common STIs found globally and investigated the current and potential role of pharmacists in provision of STI screening interventions.Discussion: There is sufficient evidence for pharmacy-based chlamydia screening, with many consumers and pharmacists finding it an acceptable and highly valued service. Some evidence was found for pharmacy-based gonorrhea, hepatitis B virus (HBV), and human immunodeficiency virus (HIV) screening. Appropriate sample collection for gonorrhea screening needs to be further examined in a pharmacy setting. HBV screening presented an increased risk of personal injury to pharmacists through the collection of whole blood specimens, which could be reduced through consumer self-sampling. Pharmacist-collected specimens for HIV is less risky as an oral swab can be used, nullifying the risk of transmission; but pre- and post-screen consultations can be time-intensive; hence, pharmacists would require remuneration to provide an ongoing HIV screening service. Not enough evidence was found for syphilis screening through community pharmacies; more studies are required that consider sampling methods other than pharmacist-collected whole blood specimens. There is no evidence to date for pharmacist-led trichomoniasis or HSV screening.Conclusion: Pharmacists are well-positioned to provide STI screening services, but further investigations are needed to overcome financial, safety, and confidentiality barriers. Keywords: pharmacist, screening, sexually transmitted infection, testing, chlamydia, gonorrhea